2010
DOI: 10.1039/c0an00191k
|View full text |Cite
|
Sign up to set email alerts
|

Protein molecularly imprinted polyacrylamide membrane: for hemoglobin sensing

Abstract: A hemoglobin sensor based on a molecularly imprinted polymer-modified electrode has been fabricated by electrochemically induced redox polymerization of acrylamide in the presence of hemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Furthermore, the great flexibility of the protein structure means that it should be polymerized under almost-native conditions so that its shape would be preserved and the binding site accurately designed. Acrylamide matrices meet these criteria [35][36][37][38]. They polymerize under mild conditions and carry uncharged functions that establish hydrogen bonds and dipole-dipole interactions with Myo [6].…”
Section: Chemical Assembly Of the Molecularly Imprinted Materialsmentioning
confidence: 99%
“…Furthermore, the great flexibility of the protein structure means that it should be polymerized under almost-native conditions so that its shape would be preserved and the binding site accurately designed. Acrylamide matrices meet these criteria [35][36][37][38]. They polymerize under mild conditions and carry uncharged functions that establish hydrogen bonds and dipole-dipole interactions with Myo [6].…”
Section: Chemical Assembly Of the Molecularly Imprinted Materialsmentioning
confidence: 99%
“…Future works with electrosynthesized pAPBA MIPs for glycoprotein recognition should consider prior immobilization of the template glycoprotein, which was found essential in obtaining satisfactory selectivity against other glycoproteins [76]. Beside biocompatibility, a wide variety of functional groups and extensive knowledge about the formed polymers motivated the use of dopamine [80,81] and acrylamide [57,82] for protein MIPs.…”
Section: Functional Monomers For the Electrosynthesis Of Protein Mipsmentioning
confidence: 99%
“…The results demonstrated that the sensor possessed not only a short response time, but also a good selectivity and binding capacity for 4-nitrophenol, which enabled the sensor with higher current response than that of non-imprinted polymer, traditional MIP, and reduced graphene oxide. Electropolymerization of monomer in the presence of protein is the favorite method for MIP based electrochemical sensors preparation to recognize and detect template protein [17][18][19]. In recent years, dopamine (DA) has attracted great interests due to its unique property of selfpolymerization in weak alkaline solution on most organic and inorganic materials [20,21].…”
Section: Introductionmentioning
confidence: 99%